The development of erosion features in cuesta relief regions - Andrade, Rafael Vilela de; Lupinacci, Cenira Maria (Revista Brasileira de Geomorfologia, 2025)
The cuesta relief is characterized by high slopes, colluvial deposits and intense evolutionary dynamics, making the region especially prone to soil degradation. This study intends to identify how the relief, lithology, and soils influence the occurrence of linear erosion processes of rill erosion, ravines and gullies in the cuestas environments. For that, the density of linear erosion features of 1972 and 2010/2011 were mapped and then analyzed in comparison with the mapped morphological features of the Cuesta in Botucatu, also prepared in this study, and lithological and soil maps from secondary sources. Quantitative and qualitative analysis identified concentrations of gullies in the cuesta reverse, at drainage headwaters, close to lithological contacts and over latosols. On the cuesta front, concentrations of rills, ravines and small gullies were identified, driven by the steep slope, colluvial covers, and transitions of heterogeneous lithologies and soils. The data demonstrated that lithological and pedological transitions, typical of cuesta regions due to high geodiversity, in addition to other conditions, are factors that enhance erosive dynamics and must be considered in territorial planning in order to preserve soils and other natural resources of these regions